Identifikasi Potensi Musculoskeletal Disorders (MSDs) pada Para Pekerja di Konveksi AA - Gustina, Delfi; Soecahyadi, Soecahyadi (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
AA Convection is a small household-scale industry that produces jeans for children. Almost the entire production process at the AA convection is manual handling. Therefore, it is necessary to identify work postures at work stations to determine the risk of injury or musculoskeletal disorders (MSDs). To identify working posture, a method is needed, one of which is the Ovako Working Posture Analysis System (OWAS) method used to identify MSDs from inappropriate work activities. This study aims to identify the risk level of MSDs. On sewing and packing work and recommending work position improvements to reduce MSD complaints to workers at AA Convection. The results of this study indicate that the risk of MSDs in sewing and packing work has the same ergonomic status, with a risk level of 2nd order, which means that action is needed for some time to come. The recommendation for improving work position in sewing work is to redesign tables and chairs according to the height of workers. While the recommendation for improving work posture in packing work is to provide work desks and chairs that can also be adjusted to body height to reduce complaints and the level of risk of MSDs.